Explaining variation in public debt: A quantitative analysis of the effects of governance - Andreas Eisl (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2017)
This paper examines the main political influence factors accounting for the variation in public debt accumulation on a global scale. This allows for a reassessment of the recent focus on a regime type theory of public debt and for a test of an alternative governance theory. I argue that political stability, the rule of law, the control of corruption, government effectiveness, and regulatory quality promote lower public debt accumulation by reducing the incentives for governments to "borrow from the future", by increasing state capacity to collect taxes and effectively use public funds, and by providing more security and equity to private investment, inducing higher economic growth and tax revenues. Both theories are tested against a number of controls stemming from theories of public choice, theories of governmental distributional conflict, as well as from politico-institutional and macroeconomic explanations of public debt accumulation. Applying different specifications of quantitative models, the two governance indicators political stability and regulatory quality show consistent effects on public debt accumulation, partly confirming the proposed governance theory. Furthermore, the paper can reproduce a public debt-reducing effect of more democratic regime types across a number of model specifications - though without a high degree of robustness.
Keywords: 330; Public debt; governance; regime type; quantitative analysis